Detailed Comparative Pharmacognostical Evaluation of Different Combinations Formulation of Triphala - G, Gopinathan (International Journal of Pharmaceutical & Biological Archive, 2013)
Detailed Comparative Pharmacognostical Evaluation of Different Combinations Formulation of Triphala